REFORMULASI ZIJ AL-KASHI PERSIA SEBAGAI HISAB AWAL BULAN KAMARIAH - Abdul Kohar (UIN ALAUDDIN MAKASSAR, 2023)
Al-kashi was a Persian astronomer who was nicknamed the second Ptolemy. The important work is zij named zij khaqani. This Zij has a deficiency in terms of the epoch or reference calculation in 851 Persia or November 16, 1481 M. This Zij has the potential to be developed so that it can be used as the initial reckoning of the lunar month. This research was conducted by Qualitative methods. Techniques for collecting data using literature. The problem the author wants to know is 1). What is the zij al-Kashi compilation algorithm? 2) How to reformulate zij al-Kashi as the initial reckoning of the Kamariyah Month? 3) how is the accuracy of Zij al-Kashi post reformulation as the initial reckoning of the month of Kamariyah? This research produces first, zij al-kashi uses Ptolemy's theory to correct the movement of celestial bodies. Al-kashi still considers the movement of celestial bodies in the form of circles instead of ellipses. Second, Reformulation is carried out by renewing the epoch, the dating system, correction for six months of movement disorders. Third, Contemporary reckoning in this case is used by Jean Meeus. Accuracy tests were carried out in critical years for the initial determination of ramdahan, Syawal Dzulhijjah. These years are 1427, 1428, 1432, and 1439. 14 The difference in the height of the modified zij al-Kashi hilal with contemporary reckoning is at intervals of 3-11 minutes of arc. The smallest difference is 3 minutes of arc and at most 11 minutes of arc.